A Comparison of Physical Abilities and Match Performance Characteristics Among Elite and Subelite Under-14 Soccer Players - Waldron, M.; Murphy, A. (Pediatric Exercise Science, 2013)
This study aimed to identify characteristics of match performance and physical ability that discriminate between elite and subelite under-14 soccer players. Players were assessed for closed performance and movement, physiological responses, and technical actions during matches. Elite players covered more total m·min-1 (115.7 ± 6.6 cf. 105.4 ± 7.7 m·min-1) and high-intensity m·min-1 (elite = 14.5 ± 2.3 cf. 11.5 ± 3.7 m·min-1) compared with subelite players. Elite players also attempted more successful (0.41 ± 0.11 cf. 0.18 ± 0.02) and unsuccessful ball retentions·min-1 (0.14 ± 0.04 cf. 0.06 ± 0.02) compared with subelite players. Elite players were faster over 10 m (1.9 ± 0.1 cf. 2.3 ± 0.2 s) and faster dribblers (16.4 ± 1.4 cf. 18.2 ± 1.1 s) compared with subelite players. Speed (10 m) and successful ball retention·min-1 contributed to a predictive model, explaining 96.8% of the between-group variance. The analysis of match performance provides a more thorough understanding of the factors underlying talent among youth soccer players.